Regulation of intracellular Ca2+ and calcineurin by NO/PKG in proliferation of vascular smooth muscle cells - LI Shi-jun; SUN Ning-ling (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
Aim: To determine whether Ca2+/calcineurin mediated the inhibitory effects of nitric oxide /cGMP-dependent protein kinase (NO/PKG) on the proliferation of vascular smooth muscle cells (VSMC). Methods: Proliferation and viability of primary VSMC from rat aorta were measured using [3-(4,5-dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide] (MTT) assay and acridine orange and ethidium bromide staining, respectively. Cytosolic Ca2+ was determined by Fluo-3/AM. Calcineurin protein and its activity were assayed using immunoblotting and free inorganic phosphate analysis, respectively. Results: (±)-S-nitroso-,N-acetylpenicillamine (SNAP) and Sp-8-(4-chlorophenylthio)-guanosine-3',5'-cyclic monophosphorothioate (Sp-8-pCPT-cGMPS) decreased phenylephrine (PE)-induced proliferation of VSMC by 27.3% and 36.6%, respectively, but Rp-8-[(4- chlorophenyl)thio]-guanosine-3',5'-cyclic monophosphorothioate (Rp-8-pCPTcGMPS) increased PE-induced proliferation of VSMC. SNAP, Sp-8-pCPT-cGMPS, and Rp-8-pCPT-cGMPS did not affect the viability of VSMC. Calcineurin protein was decreased by 63.1% and its activity was decreased by 59.7% in smooth muscle cells (SMC) pretreated with verapamil (Ver) and then stimulated by PE. In SMC pretreated with Ver, the absorbance of cells stimulated by PE decreased by 22.0% and was further inhibited by the additional treatment of SNAP and Sp-8-pCPTcGMPS. In SMC pretreated with cyclosporin A (CsA), the absorbance of cells stimulated by PE decreased by 36.7%, but could not be further altered by the additional treatment of SNAP, Sp-8-pCPT-cGMPS, and Rp-8-pCPT-cGMPS. In addition, Ver inhibited PE-induced intracellular Ca2+ variations, which could be further inhibited by SNAP and Sp-8-pCPT-cGMPS, but not by Rp-8-pCPT-cGMPS. Moreover, the increase in calcineurin activity induced by PE was inhibited by SNAP and Sp-8-pCPT-cGMPS, but was promoted by Rp-8-pCPT-cGMPS. Conclusion: NO/PKG regulates calcineurin activity via the modulation of intracellular Ca2+ concentration, and thus partially inhibits the proliferation of VSMC without affecting their viability.